Global families - Karraker, Meg Wilkes; SAGE Knowledge (Online service). (Thousand Oaks, Calif. Sage, 2013)
'Global Families' provides family scholars with a methodical introduction to the interdisciplinary field of globalization. It then examines the ways in which globalization impinges on families throughout the world in four major areas: demographic transitions, world-wide culture, international violence, and transnational employment.
Electronic reproduction.
Keywords: Families -- Study and teaching; Electronic books